Ukrainian Conference of Young Scientists and Students "Aero-2011. Air and Space Law " (November 24, 2011, Kyiv) - Сопілко, Ірина Миколаївна; Великанова, Марина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Article is devoted to the National Conference of Young Scientists and Students "Aero-2011. Air and Space Law " held on November 24, 2011 in Kyiv.